A Rare Cause of Right Upper Quadrant Pain in a 17-Year-Old Female - Nwabundo Nwankwo; Aram Barbaryan; Alaa M. Ali; Aibek E. Mirrakhimov (Case Reports in Gastrointestinal Medicine)
A 17-year-old Hispanic female presented to our hospital with complaints of right upper quadrant abdominal pain, vomiting, and fever. Physical exam was positive for hepatomegaly. Abdominal computed tomography showed multiple hypoechoic liver masses. Liver biopsy was done, which was diagnostic for hepatic epithelioid hemangioendothelioma.